Pulmonary embolism in cancer patients. Effectiveness of vitamin K antagonists and direct oral anticoagulants in long-term therapy - Nadziakiewicz, Paulina M.; Szyguła-Jurkiewicz, Bożena (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2024)
Patients with cancer are prone to develop pulmonary embolism (PE) in the course of cancer-associated thrombosis. These patients have increased risk of both recurrent venous thromboembolism and major bleeding. Pulmonary embolism treatment in the cancer patient group is challenging. Selection of anticoagulants, duration of anticoagulation, decision of adjuvant therapy, and adjustment of the regimen in special situations are the major problems that need to be considered in the treatment of cancer-associated PE. Current first line treatment in long-term therapy following an episode of PE is low molecular weight heparin (LMWH), with direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) listed as viable alternatives. This study aims to explore long-term oral anticoagulation therapy for cancer patients. Both VKAs and DOACs are compared to LMWH, which serves as a gold standard in anticoagulation therapy for cancer patients and has proven to be effective.